THE EFFECT OF PRICE DISCOUNT, ONLINE CUSTOMER RATINGS, AND ONLINE CUSTOMER REVIEWS ON CONSUMER BUYING INTEREST IN SHOPEE E-COMMERCE - Petrecia, Denanda; Hakimah, Ema (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This research seeks to examine the impact of discounted pricing, customer ratings online, and online reviews on consumers' purchasing interest within the Shopee e-commerce platform Design/Methode/Approach :This study used quntitative methods. data were collected through the use of structured questionnaires through a Likert scale from 40 respondents. Data analysis techniques include reliability tests, classical assumptions, multiple linear regression analysis, validity, F-tests and t-tests using the SPSS 25.0 program. Research Finding :The result showed that price discounts, online customer ratings, and online customer reviews significantly influenced consumer buying interest, especially gen z with a coefficient of determination of (R²) of 65,8%. Theoretical contribution/Originality :This research corroborates rhe theory that discounts, ratings, reviews affect gen z buying interest, with asimultaneous analysis of the three variables in shopee which provides new insights into young consumer behavior and effective marketing strategies Practical/Policy Implication: This research provides guidance for e-commerce businesses to focus on discount strategies and product review management, which can increase appeal among consumers and strengthen market position and consumer loyalty. Research Limitation: This research is limited to a small sample and narrow geographical coverage. Future research is recommended to explore other factors that influence purchase intention and use a larger sample to increase the generalizability of the results.